Prevalence of trachoma in the Afar Region of Ethiopia: results of seven population-based surveys from the Global Trachoma Mapping Project. (28th December 2018) - Negash, Kassahun; Macleod, Colin; Adamu, Yilikal; Ahmed, Mohammed; Ibrahim, Mohamed; Ali, Mussa; Haileselassie, Tesfaye; Willis, Rebecca; Chu, Brian K.; Dejene, Michael; Asrat, Atsbeha; Flueckiger, Rebecca M.; et al.
ABSTRACT: Purpose : Trachoma is to be eliminated as a public health problem by 2020. To help the process of planning interventions where needed, and to provide a baseline for later comparison, we set out to complete the map of trachoma in Afar, Ethiopia, by estimating trachoma prevalence in evaluation units (EUs) of grouped districts ("woredas"). Methods : We conducted seven community-based surveys from August to October 2013, using standardised Global Trachoma Mapping Project (GTMP) survey methodologies. Results : We enumerated 5065 households and 18, 177 individuals in seven EUs covering 19 of Afar's 29 woredas; the other ten were not accessible. 16, 905 individuals (93.0%) were examined, of whom 9410 (55.7%) were female. One EU incorporating four woredas (Telalak, Dalefage, Dewe, Hadele Ele) was shown to require full implementation of the SAFE strategy for three years before impact survey, with a trachomatous inflammation-follicular (TF) prevalence in 1–9-year-olds of 17.1% (95%CI 9.4–25.5), and a trichiasis prevalence in adults aged ≥15 years of 1.2% (95%CI 0.6–2.0). Five EUs, covering 13 woredas (Berahle, Aba'ala, Dupti, Kurri, Elidihare, Ayesayeta, Afamboo, Bure Mudaitu, Gewane, Amibara, Dulecho, Dalolo, and Konebo), had TF prevalences in children of 5–9.9% and need one round of azithromycin mass treatment and implementation of the F and E components of SAFE before re-survey; three of these EUs had trichiasis prevalences in adults ≥0.2%. The final EU (Mile, Ada'ar) had a sub-threshold TF prevalence and a trichiasis prevalence in adults just >0.2%. Conclusion : Trachoma is a public health problem in Afar, and implementation of the SAFE strategy is required.